Application Learning Civics for Increasing Interest in Learning in Elementary School Students - Nadia Septika (International Journal of Students Education, 2024)
This research aims to discuss the application of Civics learning to increase learning interest in elementary school students. The lack of student interest in participating in the teaching and learning process is a major problem faced by teachers and schools today. This is caused by the teacher's approach that relies too much on books as the main source, as well as the use of lecture methods that students do not utilize teaching aids or image models that can help understand the material more concretely. This research uses literature review through reviewing data by summarizing data from reference sources such as journals, books. The results showed that Civics can increase elementary students' interest in learning by means of interesting delivery by educators. Educators need to use varied and innovative learning methods and media so that students do not feel bored in learning Civics.